If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 = a Solving 43 = a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 43 + -1a = a + -1a Combine like terms: a + -1a = 0 43 + -1a = 0 Add '-43' to each side of the equation. 43 + -43 + -1a = 0 + -43 Combine like terms: 43 + -43 = 0 0 + -1a = 0 + -43 -1a = 0 + -43 Combine like terms: 0 + -43 = -43 -1a = -43 Divide each side by '-1'. a = 43 Simplifying a = 43
| 5(3/4)=x-4(1/2) | | (6p)^-1/2 | | 3-5x=4x | | tn=-5n-6 | | 6*10=an | | 1/4(×-1)=10 | | 1.4(5b+11)=19 | | -19+m=17 | | 6(1+7m)=342 | | -6d-10=20-d | | 3-23= | | 36y^2-x^4=0 | | -3m=-m | | y=3/2(0)-1 | | 2+6/2*3= | | 16*24/2*5= | | 3/4*-1/2-3/4*-3/7*-1/2*-1/4= | | 6.6x+9.6=105.9 | | (7+v)(4v+3)=0 | | Y+3=-3x-12 | | 3=n/9 | | 7cos(pi/6) | | x*2x*3x=768 | | 2m^2+8m=32 | | 10+3k=31 | | 56=8q | | 56=82 | | 2/-1/2 | | 2m^2+8m+4=36 | | 60x+50=70x | | 4x+15+6x=45 | | 8(18)=x-4(2x+8) |